2017
DOI: 10.1039/c6pp00469e
|View full text |Cite
|
Sign up to set email alerts
|

Visible light initiated release of calcium ions through photochemical electron transfer reactions

Abstract: Photolysis of anthraquinone or flavin photosensitizers in the presence of calcium EDTA complexes results in decomposition of the EDTA complex, releasing free Ca. In the case of the flavin sensitizers, it is shown that millimolar concentrations of Ca can be released using visible light (>440 nm) and with quantum yields as high as 0.31. The utility of this system is further demonstrated by in situ photogelation of an alginate solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…In another case, these authors demonstrated the efficient release of calcium ions (Ca 2+ ) from an EDTA complex facilitated by photolysis of riboflavin photocatalysts at λ irr > 440 nm. 1410 An interesting visible-light uncaging reaction using photocatalytic deboronative hydroxylation was recently reported by Chen and co-workers (one example is presented in Scheme 92. 1411 Phenol, alcohol, and amine derivatives were liberated from the corresponding boronates in high chemical yields in bacteria and mammalian cells by reaction with transient hydrogen peroxides generated in the presence of molecular oxygen using fluorescein or rhodamine derivatives as photocatalysts and ascorbate as a reductant.…”
Section: Photosensitized Release: From Small Molecules To Nanoparticl...mentioning
confidence: 97%
See 2 more Smart Citations
“…In another case, these authors demonstrated the efficient release of calcium ions (Ca 2+ ) from an EDTA complex facilitated by photolysis of riboflavin photocatalysts at λ irr > 440 nm. 1410 An interesting visible-light uncaging reaction using photocatalytic deboronative hydroxylation was recently reported by Chen and co-workers (one example is presented in Scheme 92. 1411 Phenol, alcohol, and amine derivatives were liberated from the corresponding boronates in high chemical yields in bacteria and mammalian cells by reaction with transient hydrogen peroxides generated in the presence of molecular oxygen using fluorescein or rhodamine derivatives as photocatalysts and ascorbate as a reductant.…”
Section: Photosensitized Release: From Small Molecules To Nanoparticl...mentioning
confidence: 97%
“…The authors proposed photodeprotection mechanisms involving both oxidative and reductive quenching scenarios (Scheme ) corresponding to the general mechanism shown in Scheme d. In another case, these authors demonstrated the efficient release of calcium ions (Ca 2+ ) from an EDTA complex facilitated by photolysis of riboflavin photocatalysts at λ irr > 440 nm …”
Section: Photosensitized Release: From Small Molecules To Nanoparticl...mentioning
confidence: 99%
See 1 more Smart Citation
“…4The rate of Ca 2+ release is >20 times faster than those for riboflavin and enzyme catalysts, UV irradiation, and diffusion from a CaSO 4 slurry ( Supplementary Fig. 11) 19,[33][34][35] . These advantages facilitate the rapid, large-scale fabrication of hydrogels, which is highly desirable for industrial applications.…”
Section: Resultsmentioning
confidence: 99%
“…Photoreleased molecules are of considerable interest not only in the field of photochemistry but also in site‐specific delivery applications . Current literature on sensitizer and drug photorelease has mainly focused on the use of direct UV, visible and near‐IR light to activate the release mechanisms.…”
Section: Introductionmentioning
confidence: 99%